Higher-order income risk over the business cycle - Christopher Busch; Alexander Ludwig (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We extend the canonical income process with persistent and transitory risk to shock distributions with left-skewness and excess kurtosis, to which we refer as higher-order risk. We estimate our extended income process by GMM for household data from the United States. We find countercyclical variance and procyclical skewness of persistent shocks. All shock distributions are highly leptokurtic. The existing tax and transfer system reduces dispersion and left-skewness of shocks. We then show that in a standard incomplete-markets life-cycle model, first, higher-order risk has sizable welfare implications, which depend crucially on risk attitudes of households; second, higher-order risk matters quantitatively for the welfare costs of cyclical idiosyncratic risk; third, higher-order risk has non-trivial implications for the degree of self-insurance against both transitory and persistent shocks.
Keywords: D31; E24; E32; H31; J31; 330; Labor Income Risk; Business Cycle; GMM Estimation; Skewness; Persistent and Transitory Income Shocks; Risk Attitudes; Life-Cycle Model